General geology and the impact of non-point source pollution on Sungai Betis, Kampung Lambok - Fadli Johari (2013)
Non-point source pollution come from wide area and many diffuse sources which make it hard to be control with. The purposes to conduct this study are to update the geological map of Kampung Lambok, to determine the type of pollutant in Sungai Betis, Kampong Lambok and to classify the water quality of Sungai Betis, Kampung Lambok. The present study area is a part of Gua Musang which is latitude between 4'52"O'N and 4'54"O'N and longitude between 101'44"30'E and 101'47"0'E. In the research the methods were used for the geological mapping was traversed and structural analysis while the chemical analysis of river water were done by in-situ analysis using Multi-parameter YSI instruments which the data recorded are Temperature (T), Conductivity (C), Total Dissolved Solid (TDS), Dissolved Oxygen (DO) and ph Value and for Sodium (Na), Magnesium (Mg) and Calcium (Ca), the analysis was done in lab by using Atomic Adsorption Spectrophotometer (AAS). From the above analysis, all the river water samples were classified into class II of Interim National Water Quality Standards (INWQS). This mean the river water from Sungai Betis were suitable for recreational uses with body contact and also for irrigation purposes.